Formulation and Evaluation of Novel Aceclofenac Matrix Tablet Using Natural Polymers - Kumar, Rajesh; Sharma, Dr. Vijay; Kumawat, Sunil (Journal of Biomedical and Pharmaceutical Research, 2023)
The current study attempted to design and create Aceclofenac sustained release matrix tablets employing different proportions of Hibiscus rosa-sinensis mucilage, Mimosa Pudica mucilage as natural polymers and povidone.Aceclofenac is widely used as a centrally acting muscle relaxant; therefore, have been selected to prepare sustained release dosage forms.Different types of evaluation parameters were evaluated like appearance, thickness, diameter, weight variation, hardness, friability, drug content, in-vitro dissolution studiesand stability studies.Sustained release matrix tablets can improve patient compliance by lowering the total dose and dosing schedule, which can be extremely beneficial in the treatment of chronic illnesses.Key words:S, , .